Analisis SIMRS Dengan Metode PIECES Di RSU Dr. H. Koesnadi Bondowoso - Finno Harta Dinata; Atma Deharja (Jurnal Kesehatan, 2020)
Hospital Information System (HIS) is an important component to improve hospital service quality. HIS  at General Hospital Dr. H. Koesnadi Bondowoso has been running for about 5 years since 2015. HIS implementation is not optimal because there are still various problems in its implementation.  The problem such as errors in printing reports so users must create reports manually. This research was aimed to analyze the application of hospital information systems using the PIECES method. This type of research is qualitative. It showed that the information Hospital Information System (HIS) performance results based on aspects of performance Hospital Information System (HIS) performance goes according to user needs, information aspects of information generated accurately, aspects of economics have produced economic value, running control aspects related to control and system security, efficiency aspects have provided efficiencies in its application, service aspect has made it easy for system users. Based on aspects of Performance, Information, Economic, Control, Efficiency, and Service Hospital Information System (HIS) performance has been running according to user needs, but it is not free from various problems, so there needs a efforts to improvement and development of Hospital Information System (HIS) through the recommendation of researchers so that Hospital Information System (HIS) can maintain quality and improve service quality to patients.